Study of heat and mass transfer processes in an oil well with a bottomhole heater of different length - Pinyagin, Dmitriy Sergeyevich; Trufanova, Nataliya Mikhaylovna; Kostarev, Nikita Aleksandrovich (Computational Continuum Mechanics, 2024)
This paper considers a three-dimensional mathematical model of heat and mass transfer in an oil well with a bottom-hole heater. The vertical section of an oil well with an electric bottom-hole heater device for wells with highly viscous and paraffinic oil was investigated. The bottomhole heater is a monolithic cylinder located in the lower part of the tubing. The tubing contains perforations through which the oil fluid enters the tubing. The use of a local heater in the near-wellbore area makes it possible to increase the temperature of the fluid flowing through it, thereby reducing the viscosity of the oil and the load on the electric centrifugal pump, for which the critical value of the viscosity of the pumped medium is determined. The implementation of this model was carried out by the finite volume method using the ANSYS engineering simulation software. The geometry of finite elements and the finite volume mesh generated, an analogue of a continuous computational domain, were constructed by the MESH preprocessor. The finite volume mesh consists of polyhedral elements. Using the model, the fields of temperature, velocity and viscosity were obtained throughout the entire volume of the area under study. The curves showing the dependence of the average temperature of the cross section on the longitudinal coordinate of the tubing and the dependence of the average temperature at the inlet to an electric centrifugal pump on the heater power are presented. The viscosity value at the maximum permissible temperature of the heater, as well as the value of sufficient heater power to ensure uninterrupted pumping of petroleum liquid, were determined. The results obtained can be used to significantly improve the operating efficiency of an electric centrifugal pump, to increase the turnaround time and to reduce material costs during field development.